2023
DOI: 10.1021/jacs.2c08596
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Droplet Aging and Seeded Fibril Formation of the Cytotoxic Granule Associated RNA Binding Protein TIA1 Low Complexity Domain

Abstract: Protein domains biased toward a few amino acid types are vital for the formation of biomolecular condensates in living cells. These membraneless compartments are formed by molecules exhibiting a range of molecular motions and structural order. Missense mutations increase condensate persistence lifetimes or structural order, properties that are thought to underlie pathological protein aggregation. In the context of stress granules associated with neurodegenerative diseases, this process involves the rigidificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…[25][26][27][28][29][30] It has also recently been employed in the context of phase separation. [31][32][33][34][35][36][37] A particular strength of NMR is the possibility to distinguish different polymorphs, which are often observed in the context of amyloid fibrils [25,38,39] and may be of relevance in the context of LST. We performed structural solid-state NMR studies, complemented with transmission electron microscopy (TEM), atomic-force microscopy (AFM) and X-ray diffraction, of several model peptide derivatives with an XXssXX motif, in which two dipeptide sticker moieties (XX) are linked together via a flexible disulphide bond.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[25][26][27][28][29][30] It has also recently been employed in the context of phase separation. [31][32][33][34][35][36][37] A particular strength of NMR is the possibility to distinguish different polymorphs, which are often observed in the context of amyloid fibrils [25,38,39] and may be of relevance in the context of LST. We performed structural solid-state NMR studies, complemented with transmission electron microscopy (TEM), atomic-force microscopy (AFM) and X-ray diffraction, of several model peptide derivatives with an XXssXX motif, in which two dipeptide sticker moieties (XX) are linked together via a flexible disulphide bond.…”
Section: Introductionmentioning
confidence: 99%
“…Solid‐state NMR under magic‐angle spinning (MAS) is the method‐of‐choice to study protein samples in macroscopically condensed phases and has been particularly successful to determine the structures of a variety of amyloid fibrils [25–30] . It has also recently been employed in the context of phase separation [31–37] . A particular strength of NMR is the possibility to distinguish different polymorphs, which are often observed in the context of amyloid fibrils [25,38,39] and may be of relevance in the context of LST.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, TIA-1 expression levels in the brain's hippocampus are implicated in synaptic plasticity and behavior in mice 41 . TIA-1 undergoes liquid-liquid phase separation and subsequent amyloid bril formation 42,43 , and the selfassembly mechanism underlies stress granule formation and possibly other physiological functions 35,44,45 . On the other hand, pathological deposits of TIA-1 coaggregated with huntingtin or phosphorylated tau have been identi ed in brain tissue from mouse models of tauopathy and Huntington's disease, as well as from Alzheimer's disease patients 46,47 .…”
Section: Introductionmentioning
confidence: 99%
“…These results imply that TIA-1 has the potential to serve as a platform for amyloid bril formation.According to genetic analysis of ALS, frontotemporal dementia (FTD) and Welander distal myopathy (WDM), TIA-1 was found to carry diseaseassociated mutations in its IDP region, the prion-like domain (PLD) 42,48,49 . Although these mutations were shown to alter the self-assembly property of TIA-1 42,43,50 , the structural basis of amyloid bril formation has not been elucidated. In this study, we investigated the amyloid bril structure formed by human wild-type TIA-1 PLD and found that amyloid brils have structural features that ensure reversibility, including a kinked backbone conformation, a polar zipper, and a proline-mediated cross-b motif.…”
mentioning
confidence: 99%
“…This approach enables the characterization of both flexible and rigid protein components to gain a comprehensive molecular view of the complex HP1α–nucleosome system. In addition, solid-state magic angle spinning (MAS) NMR spectroscopy is ideally suited for the analysis of viscous heterogeneous environments such as liquid droplets and gels, ,, thus providing the opportunity to understand how these environments shape nucleosome structure and dynamics. Using these spectroscopic tools, we dissect the interactions of the CD domain and the CSD dimer with the nucleosome and capture the effect of HP1α phase separation on the nucleosome core and tails.…”
Section: Introductionmentioning
confidence: 99%